2011
DOI: 10.1128/aem.00623-11
|View full text |Cite
|
Sign up to set email alerts
|

Rapid-Viability PCR Method for Detection of Live, Virulent Bacillus anthracis in Environmental Samples

Abstract: In the event of a biothreat agent release, hundreds of samples would need to be rapidly processed to characterize the extent of contamination and determine the efficacy of remediation activities. Current biological agent identification and viability determination methods are both labor-and time-intensive such that turnaround time for confirmed results is typically several days. In order to alleviate this issue, automated, high-throughput sample processing methods were developed in which real-time PCR analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 18 publications
0
62
0
Order By: Relevance
“…44 Results of the ring trial confirmed the results obtained in the in silico analysis ( Table 4). The three assays with highest in silico specificity (BA5345, 21 PL3, 47 and BA5357 46 ) all performed well in the ring trial, with diagnostic sensitivity and specificity values close to 1 ( Table 5). Furthermore, these assays were found to be robust and provided consistent results between laboratories (kappa values of 0.9-1.0).…”
Section: Ring Trialmentioning
confidence: 98%
See 3 more Smart Citations
“…44 Results of the ring trial confirmed the results obtained in the in silico analysis ( Table 4). The three assays with highest in silico specificity (BA5345, 21 PL3, 47 and BA5357 46 ) all performed well in the ring trial, with diagnostic sensitivity and specificity values close to 1 ( Table 5). Furthermore, these assays were found to be robust and provided consistent results between laboratories (kappa values of 0.9-1.0).…”
Section: Ring Trialmentioning
confidence: 98%
“…30 These genetic markers provide limited specificity and require additional timeconsuming and labor-intensive post-PCR analysis steps. Other areas of the chromosome have also been investigated as potential DNA-targets for identification purposes, including the so-called BA813 [31][32][33][34][35][36][37][38] and BA5510 sequences, 19 genes bclB, 39 sap, 40,41 saspB, 5,42 and sspE, 22,43 the B-type small acid-soluble spore protein gene (SASP), 44 a glycosyltransferase group 1 family protein, 45 a protein showing similarities with an abhydrolase, 18 and several DNA loci located on prophage regions, 17 i.e., BA5345, 21 BA5357, 46 and PL3. 47 Although most of these regions have been claimed to be anthrax-specific, B. cereus strains sometimes yield false positive results.…”
Section: Literature Survey Of Pcr-based Detection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the 2001 bioterrorism-associated anthrax outbreak, several different types of real-time PCR assays for the detection of B. anthracis have been developed (11,12,24,28). The molecular beacon-based assay utilized in this study was selected to assess whether recovery of B. anthracis with the three swab extraction methods would be consistent irrespective of the type of real-time PCR assay used.…”
Section: Discussionmentioning
confidence: 99%